IMPLEMENTASI HASIL AUDIT LAPORAN KEUANGAN DALAM MENUNJANG EFISIENSI DAN EFEKTIVITAS PENGELOLAAN KEUANGAN (Studi Kasus di PT Astra Graphia Tbk Implementasi Audit Operasional Sistem Online) - Vanina, Maria Vanina; Fibriany, Firstianty Wahyuhening; Wijaya, Darma (FEB-UP Press, 2024)
With the growing development of a company, the problems faced by the company also increase. The limitations of a leader in controlling and supervising the company's activities require the leader to delegate some authority to his subordinates. Therefore, leaders need a tool that can assess and evaluate company activities. The tool that can be used for this purpose is the implementation of operational audits. By conducting an operational audit, the company hopes to improve the efficiency and effectiveness of the part being audited. Based on the problems above, the authors conducted research at PT Astra Graphia Tbk, which is engaged in information technology and focuses on printing and digital services business activities. This research uses a descriptive method with a qualitative approach. Primary data is obtained from data collection, and secondary data is obtained from literature, books, and company documents. Keywords: Audit, Financial Statements, Sales Efficiency and Effectiveness